Pengaruh E-WOM dan Brand Image Terhadap Keputusan Pembelian dengan Brand Trust sebagai Variabel Mediasi Produk Kosmetik di Kalangan Follower Akun Instagram @somethingofficial - Janet Devagaluh Athalla; Tanti Hermawati (Universitas Sebelas Maret (UNS), 2026)
The growth of digital platforms has changed how people behave as a consumers and opened new ways for brands to promote their products, especially on social media like Instagram. This study aims to analyze how electronic word of mouth (e-WOM) and brand image influence purchase decisions with brand trust as a mediating variable. The research focuses on followers of Somethinc’s official Instagram account. This study uses a descriptive quantitative method with data collected through questionnaire. A total of 100 respondents who follow Somethinc on Instagram participated. The data were analyzed using multiple linear regression and the Sobel test to examine both direct and indirect effects. The results show that e-WOM and brand image have a significant positive effect on brand trust. Brand trust also has a significant effect on purchase decisions. Moreover, brand trust plays a significant role in mediating the relationship between e WOM and brand image on purchase decisions. These findings highlight that building brand trust through positive e-WOM and a strong brand image can help increase consumers intention to buy.